PROGRAM SCIENCES KIDS COMMUNITY BERBASIS GROUP INVESTIGATION UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA MADRASAH IBTIDAIYAH - Anggun Zuhaida (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2018)
The Science Kids Community program is implemented using Group Investigation (GI) model which is part of cooperative learning. This study aims to explain the implementation of the Science Kids Community program based on GI and also to determine the results of improving problem-solving skills in students. This research is focused on the implementation of science learning in Madrasah Ibtidaiyah (MI) students. The method used in this research is descriptive with qualitative approach. Instruments in this study, using questionnaire, problem solving test, and interview. Subjects in this study were the students of 5th class MI NU Miftahul Ulum 2 Kudus. The implementation of the Science Kids Community program with the GI model provides wider opportunities and authority for students to jointly solve problems of science learning. The results of problem solving skills, focused on 2 groups of students, namely students with high motivation category (category A) and students with moderate motivation category (category B). Obtained results, in Category A students: the maximum at the stage identify the problem, define the purpose, and execute the strategy. While the category B students, the new maximum at the stage of implementing the strategy. This can make the input for teachers, to more often implement group-based learning model / community to be able to improve students problem solving skills